Audience Reception in Digital Spaces: Interpreting Domestic Gender Roles in the “Suami Sejati Masak” YouTube Campaign - rizky kertanegara (ULTIMA Comm, 2025)
Advertising increasingly functions not only as a commercial tool but also as a cultural text through which social values are communicated and negotiated. One emerging theme in contemporary campaigns is gender equality, particularly in the representation of domestic roles. This study examines how audiences interpret gender equality messages in the “Suami Sejati Masak” campaignby Heinz ABC Indonesia, focusing on user-generated comments on YouTube. Adopting a qualitative approach within a constructivist paradigm, this research applies reception analysis, based on Stuart Hall’s encoding/decoding framework, to 25 selected comments posted between March 2020 and July 2021. The findings reveal a range of audience interpretations, categorized as dominant, negotiated, and oppositional. Dominant readings indicate acceptance and reinforcement of shared domestic roles, while negotiated readings reflect ambivalence shaped by practical considerations and everyday constraints. Oppositional readings highlight resistance grounded in traditional gender norms and perceptions of realism.